Peran Persepsi Dukungan Sosial Terhadap Tingkat Stress Akademik Pada Mahasiswa Yang Sedang Mengerjakan Skripsi - Putri, Nabila Noorandrea; Primatia Yogi Wulandari (CV RIFAINSTITUT, 2023)
The thesis is considered a stressor which is considered to influence students' academic stress levels. One of the factors that is considered to influence the level of academic stress is the perception of social support that students have, so this research was conducted with the aim of finding out whether there is an influence that the perception of social support has on the academic stress of students who are working on their thesis. This research is quantitative research using survey methods and purposive sampling techniques for sampling. The number of respondents was 100 people consisting of students who were working on their thesis. The measuring instrument used in this research is a measuring instrument compiled by Gadzella and Masten (2005) and adapted by Jehan (2017) for the academic stress variable and a measuring instrument compiled by Romi (2022) for the perception of social support variable. The data obtained was processed using a simple linear regression technique and showed the results that there was a role of perceived social support in the academic stress of students who were working on their thesis. Research shows that there is an influence of perceived social support on the academic stress of students who are working on their thesis. The role given by the perception of social support is 10.1%. It can be concluded that perceived social support influences a small percentage of a person's level of academic stress and the rest is influenced by other variables.